Women’s Resistance to Patriarchy in the Little Women Movie by Greta Gerwig - Ayu Sulistiawati; Ujang Suyatman; Agry Pramita (Universitas Islam Negeri Palopo, 2026)
This study examines the representation of patriarchy and women’s resistance in the film Little Women (2019) directed by Greta Gerwig. The research aims to analyze how patriarchal norms are portrayed in the film and how the female characters respond to these constraints. The study is grounded in feminist theory, particularly Simone de Beauvoir’s existential feminism, which emphasizes women’s agency in defining their own identities and freedom. This research employs a qualitative descriptive method, using the film as the primary data source. Data were collected through purposive sampling of selected scenes that depict gender relations, dialogue, narrative actions, and visual elements associated with patriarchal structures and acts of resistance. The analysis focuses on cinematic aspects such as dialogue, characterization, spatial arrangement, costume, and symbolic imagery. The findings show that patriarchy in the film is represented through social expectations that prioritize marriage as women’s ultimate goal, limit women’s professional independence, and reinforce traditional domestic roles. Nevertheless, the March sisters challenge these restrictions through different forms of resistance. Verbal resistance appears through dialogue that rejects patriarchal norms, symbolic resistance emerges through creative and intellectual pursuits, and relational resistance is reflected in the solidarity and mutual support among the sisters. The study concludes that the film portrays women as active agents who negotiate autonomy and redefine their identities within patriarchal constraints.